The Decadent City: Urban Space in Latin American Dirty Realist Fiction - Fudacz, Jamie Diane (eScholarship, University of California, 2012)
This dissertation explores the treatment of urban spaces in Latin American dirty realist fiction from the 1990's to the present, focusing on the works of Guillermo Fadanelli (Mexico), Fernando Vallejo (Colombia), and Pedro Juan Gutiérrez (Cuba). Whereas Fadanelli centers his works in the megalopolis of a Mexico City straining under the pressures of rapid modernization and development, Gutiérrez depicts a Havana crumbling during the economic crises of the Special Period, and Vallejo portrays Medellín as utterly degraded by drug trafficking and its associated violence. All three authors, however, employ the gritty, almost visceral dirty realist style to best depict poverty-stricken societies populated by unexceptional individuals in a quest for survival in a rapidly transforming and decaying urban landscape. This dirty realist space is thus primarily defined by abjection and the uncomfortable coexistence of a focus on distinctive local minutia and the homogenizing effects of global, postmodern consumer society, a phenomenon accompanied by the proliferation of non-places as defined by Marc Augé. In these non-places, the meta-narratives of family, religion and nation that previously marked spaces of identity formation no longer function, leaving a sense of purposelessness. While there exists some nostalgia for the spaces that produced and reproduced these previous narratives, these spaces also prove to be marginalizing and have contributed to the city's current state of violence and decay. In light of the negative meanings ascribed to earlier spaces of individual and community identity formation, the evacuation of all meaning from these spaces has a positive connotation. Even though the manner in which these dirty realist authors are conceptualizing the urban space shows this new space to be decadent, empty, and violent, its transitional nature and the questioning of previous narratives that it implies open room for the creation of a new type of space that could grow to be more inclusive, even if this is never accomplished within the narratives themselves.
Dissertation, eScholarship, University of California, 2012